Procedures and Requirements for Submitting People's Business Credit (KUR) to Support the Development of Customer MSMEs at PT Bank Rakyat Indonesia (Persero) Batanghari Branch Office - Azizah, Aisyah Hasna; Feny Tialonawarmi (Journal of Humanities, Community Service, and Empowerment, 2025)
People's Business Credit (KUR) is one of the government programs that aims to support the Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia. This program offers access to capital at low interest rates for MSMEs that require assistance in developing their businesses. This study examines the procedures and requirements for submitting KUR at PT Bank Rakyat Indonesia (Persero) KCP Batanghari, as well as an evaluation of its implementation and impact on the development of micro, small, and medium-sized enterprises (MSMEs). The primary focus of this study is to identify factors that influence the eligibility of MSMEs to receive KUR, as well as how this program supports the growth of the small business sector in Indonesia. The study's results show that, although the KUR program has made a significant contribution to supporting the development of MSMEs, challenges remain in its implementation. Several factors, including a complicated application process, a lack of understanding of the requirements, and limited information about the program, are the main obstacles. However, the success of payment restructuring and training for KUR recipients has shown a positive impact on the ability of MSMEs to develop. Therefore, evaluation and improvement of procedures, as well as further counseling, are needed for MSME actors to optimize the benefits of KUR for the MSME sector.